Building stronger futures: Educational awareness for quality families in Ibul Village, West Bangka Regency - Hikmawati, Agci; Suryadin, Asyraf; Haiyudi, Haiyudi (Universitas Muhammadiyah Magelang, 2025)
Family is the first environment that determines the quality of children’s education. Quality family guidance and counseling are needed to support the goals of national education as stated in the National Education System Law No. 20 of 2003. Therefore, this counseling aims to raise family awareness of the importance of education for children in Ibul Village, Simpang Teritip District, West Bangka Regency. The method used in this community service program involves mentoring and counseling techniques. The results obtained from this community service program include a growing awareness among parents and prospective parents regarding the importance of their role and the tasks and functions of the family. The eight family functions explained in this activity broaden the community’s insight into improving the quality of education, both morally and intellectually. The evaluation results show an increase in parental awareness of the importance of communication and educational guidance for children.